Implementasi Metode TOPSIS pada Sistem Pendukung Keputusan Penilaian Kinerja Guru di SMKN 10 Bulukumba - Lut Faizal; Irfan Irfan (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2025)
A TOPSIS-based decision support system (SPK) was developed to objectively assess teacher performance at SMKN 10 Bulukumba. This research analyzed four criteria: pedagogical skills, attendance, teaching methods, and professional attitude. The TOPSIS method was used to calculate preference scores based on relative closeness to the ideal solution, resulting in accurate ranking. As a result, 3 teachers achieved the highest scores, demonstrating optimal performance across all criteria. The implementation of TOPSIS proved its ability to reduce subjective bias and increase transparency of assessment. Schools can identify teachers' strengths and areas of improvement through analysis of criteria scores. The system also cuts evaluation time from weekly to daily, improving management efficiency. The research findings confirm TOPSIS as a reliable evaluation tool that supports teachers' professional development through data-driven feedback. Practical implications include recommendations for the adoption of similar systems in other educational institutions with criteria customization. This study contributes to the field of education management by presenting a scalable solution to improve accountability and teaching quality, while offering an adaptive framework for technology-based performance evaluation.